The Nectin family ligands, PVRL2 and PVR, in cancer immunology and immunotherapy - Murakami, Kosuke; Ganguly, Sudipto (Frontiers in Immunology, 2024)
In recent years, immunotherapy has emerged as a crucial component of cancer treatment. However, its efficacy remains limited across various cancer types, highlighting unmet needs. Poliovirus receptor-related 2 (PVRL2) and Poliovirus receptor (PVR) are members of the Nectin and Nectin-like Molecules family, known for their role as cell-cell adhesion molecules. With the development of immunotherapy, their involvement in tumor immune mechanisms as immune checkpoint factors has garnered significant attention. PVRL2 and PVR are predominantly expressed on tumor cells and antigen-presenting cells, binding to PVRIG and TIGIT, respectively, which are primarily found on T and NK cells, thereby suppressing antitumor immunity. Notably, gynecological cancers such as ovarian and endometrial cancers exhibit high expression levels of PVRL2 and PVR, with similar trends observed in various other solid and hematologic tumors. Targeting these immune checkpoint pathways offers a promising therapeutic avenue, potentially in combination with existing treatments. However, the immunomodulatory mechanism involving these bindings, known as the DNAM-1 axis, is complex, underscoring the importance of understanding it for developing novel therapies. This article comprehensively reviews the immunomodulatory mechanisms centered on PVRL2 and PVR, elucidating their implications for various cancer types.